(untitled) (Revista Argentina de Musicología, 2018)
The idea of an African component of the tango is based on overlapping issues of origin and subsequent additions, but there is no consensus. The Antología del Tango Rioplatense adopts an ambiguous position: supports the participation of Afro-American people in the origin, but discards the Afro-American musical influence. After over a hundred years, Africanity of tango can be very controversial because during that time the Afro-Argentinean community contributed very little to the development of the genre. Consequently, the positions defending Africanity of tango generate skepticism among the musicological community. My proposal is to review the arguments of the Antología. . . considering recent studies on African-American music. I arrive to the conclusion that tango is most likely steeped with an Afro-American component which with successive composers and performers might have played, even without being fully aware of it.